Bandgap-opened bilayer graphene approached by asymmetrical intercalation of trilayer graphene - Zhan, Da (2015)
A novel graphene structure formed by asymmetrical intercalation of FeCl3 molecules into a trilayer graphene is reported. The trilayer graphene is divided into a single layer and a bilayer graphene by the inserted FeCl3 layer. Theoretical calculation shows that such graphene bilayers with broken inversion symmetry present a prominent opened bandgap of ∼0.13 eV.